Environmental awareness and benefits of industrialized building systems (IBS) - Ahmad Bari, Nor Azmi; Abdullah, Nor Ainah; Yusuff, Rosnah; Ismail, Napsiah; Jaapar, Aini (Elsevier, 2012)
A comparative study was conducted between IBS construction and conventional wet construction to compare performances in terms of time, cost, quality and utilization of manpower. Four low-rise building projects which adopted IBS and conventional methods of construction were selected for case studies. The findings suggest that construction using inter-locking blocks and prefabricated systems can reduce the overall cost, time, manpower and produces better quality housing than the conventional method. Environmentally, IBS also facilitates waste minimization and reduction, thus further highlighting its positive economics, while reductions in overall manpower requirements may also bring about less dependency on foreign labour.